Comparative Study of Macro-elements (P, Na and K) in the Edible Part of Vegetables Irrigated with Sewage, Canal and Tube Well Water - Haroon, Muhammad; Vaqas, Muhammad; Adnan Iqbal, Muhammad (Asian Journal of Chemistry, 2012)
The study was undertaken to compare the concentration of macro elements (P, Na and K) in edible part of the twelve different species of vegetables, irrigated with three different water sources. It was found that the accumulation of macro elements (P, Na and K) in the edible part of plants occurs in the order of: sewage > canal > tube well water.